Research on the contribution of shale gas development and utilization in Sichuan Province to carbon peak based on the PSA process - Tian Feibo (Nonlinear Engineering, 2025)
Shale gas plays a crucial role in China’s energy transition and carbon peak goals, with Sichuan Province being a key development region. However, challenges such as methane (CH4) emissions and inefficient carbon capture hinder its sustainable utilization. Traditional static methods for gas separation, while effective under stable and simplified conditions, often struggle to adapt to complex and fluctuating working environments typically encountered in shale gas extraction, such as variable pressure, temperature, and gas composition. These limitations reduce their efficiency and reliability in large-scale, real-world applications. In contrast, the pressure swing adsorption (PSA) process offers a dynamic and adaptable solution for CO2 separation and CH4 purification, performing more efficiently under varying operational conditions. This study evaluates the contribution of shale gas development in Sichuan to China’s carbon peak targets, with a focus on optimizing the PSA process. Using life cycle assessment and real-world operational data, we quantify the carbon footprint and analyze PSA parameters under different working conditions to improve CO2 capture efficiency. Results show that optimized PSA not only significantly reduces emissions compared to static methods under variable conditions but also supports China’s carbon reduction strategy. The findings provide theoretical and practical insights for policymakers and industry stakeholders in achieving sustainable shale gas utilization.